Artemis : goddess of hunting and protector of animals - Temple, Teri.; Squier, Robert (Mankato, MN : Child's World, 2013)
An introduction to Greek mythology that shares the stories and myths about the Greek goddess Artemis, goddess of hunting and protector of animals.
Includes bibliographical references (p. 32) and index.
Library Media Connection
Library Media Connection, May 2013
4.4
3-6.
3-6
Keywords: Artemis (Greek deity) -- Juvenile literature; Mythology, Greek -- Juvenile literature; Artemis (Greek deity); Mythology, Greek; Artemis (Greek deity); Greek mythology